Animal models of hyperandrogenism and ovarian morphology changes as features of polycystic ovary syndrome: a systematic review. Issue 1 (December 2017) - Paixão, Larissa; Ramos, Ramon; Lavarda, Anita; Morsh, Debora; Spritzer, Poli
Abstract Polycystic ovary syndrome (PCOS) is a common endocrine disorder, affecting 9–18% of women in reproductive age that causes hyperandrogenism and infertility due to dysfunctional follicular maturation and anovulation. The etiology of PCOS is still poorly known, and information from experimental animal models may help improve current understanding of the mechanisms of PCOS initiation and development. Therefore, we conducted a systematic review of currently available methods for simulation of PCOS in experimental models, focusing on two main endocrine traits: ovarian morphology changes and circulating levels of sex hormones and gonadotropins. We searched the MEDLINE database for articles in English or Spanish published until October 2016. Of 933 studies identified, 39 were included in the systematic review. One study compared interventions with androgens versus estrogens, 18 used androgen-induced stimulation, 9 used estrogens or drugs with estrogen action, including endocrine disruptors, to induce PCOS-like models, and 12 used miscellaneous interventions. Broad differences were found among the studies concerning hormonal interventions, animal species, and developmental stage at the time of the experiments, and most models resulted in ovarian morphology changes, mainly increases in the number of cystic and antral follicles and decreases in the corpus luteum. Hyperandrogenism was produced by using androgens and other drugs as the stimulatory agent. However, studies using drugs with estrogenic effect did not observe changes in circulating androgens. In conclusion, medium- or long-term testosterone administration in the pre- and postnatal periods performed best for induction of a PCOS-like phenotype, in rhesus macaque and rat models respectively. In rats, postnatal exposure to androgens results in reprogramming of the hypothalamic-pituitary-ovarian-axis. Thus, comparisons between different intervention models may be useful to define the timing of reproductive PCOS phenotypes in experimental animal models.